Sinergitas Kemitraan melalui Pelatihan Media Digital Marketing bagi Pengrajin Batik Bono - Wirman, Welly; Wahidar, Tutut Ismi; Yozani, Ringgo Eldapi; Ismandianto, Ismandianto; Zurani, Ikhma (MENARA RIAU, 2024)
Batik Bono is a work of art typical of Pelalawan district which has various motifs including Batik Kloso, Batik Sekijang and so on. The aim of this service is so that technological advances can be enjoyed by everyone, especially regional Batik craftsmen, to be able to adapt and maximize existing potential. In this case, the service team uses the method of implementing lectures and digital marketing media practices to help craftsmen market their products digitally so they can reach national and international markets. Realizing the limited human resources of Batik craftsmen in Pelalawan Regency, especially in using digital media to increase marketing of Bono Batik products, the service team collaborated with the Pelalawan Regency Manpower Service. From the results of the service, there are 50 Batik craftsmen spread across Pelalawan district. This dedication is a potential collaboration between the Riau Andalan Pulp and Paper (RAPP) company and the Pelalawan Regency Tourism Office to advance the business of Bono Batik craftsmen in the future.